2020
DOI: 10.3390/ijms21062104
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2 Signaling in the Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells Induced by Pulsed Electromagnetic Fields

Abstract: Pulsed electromagnetic fields (PEMFs) are clinically used with beneficial effects in the treatment of bone fracture healing. This is due to PEMF ability to favor the osteogenic differentiation of mesenchymal stem cells (MSCs). Previous studies suggest that PEMFs enhance the osteogenic activity of bone morphogenetic protein-2 (BMP2) which is used in various therapeutic interventions. This study investigated the molecular events associated to the synergistic activity of PEMFs and BMP2 on osteogenic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Several studies demonstrated that PEMFs stimulation significantly increases the pro-osteogenic activity of members of the TGF-β gene family, including BMP-2 and -4. Recently, in human bone marrow MSCs (hBM-MSCs), Martini et al confirmed the combined osteogenic activity of PEMFs and BMP-2 [ 55 , 56 , 66 ], in the presence of low doses of BMP-2. Furthermore, the authors showed that the PEMFs effects were associated to increased gene expression of several BMP signaling components including BMP-2, BMP-6, BMP type I receptor, and to the activation of SMAD1/5/8, the main player in the canonical BMP signaling pathway [ 66 ].…”
Section: Osteogenic Effects and Pathways Activated By Pulsed Electmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies demonstrated that PEMFs stimulation significantly increases the pro-osteogenic activity of members of the TGF-β gene family, including BMP-2 and -4. Recently, in human bone marrow MSCs (hBM-MSCs), Martini et al confirmed the combined osteogenic activity of PEMFs and BMP-2 [ 55 , 56 , 66 ], in the presence of low doses of BMP-2. Furthermore, the authors showed that the PEMFs effects were associated to increased gene expression of several BMP signaling components including BMP-2, BMP-6, BMP type I receptor, and to the activation of SMAD1/5/8, the main player in the canonical BMP signaling pathway [ 66 ].…”
Section: Osteogenic Effects and Pathways Activated By Pulsed Electmentioning
confidence: 99%
“…Recently, in human bone marrow MSCs (hBM-MSCs), Martini et al confirmed the combined osteogenic activity of PEMFs and BMP-2 [ 55 , 56 , 66 ], in the presence of low doses of BMP-2. Furthermore, the authors showed that the PEMFs effects were associated to increased gene expression of several BMP signaling components including BMP-2, BMP-6, BMP type I receptor, and to the activation of SMAD1/5/8, the main player in the canonical BMP signaling pathway [ 66 ]. Synergistic effects on osteogenic differentiation of periodontal ligament stem cells (hPDLSCs) have been also observed following combined treatment of PEMFs and BMP-9, another component of the BMP family [ 63 ].…”
Section: Osteogenic Effects and Pathways Activated By Pulsed Electmentioning
confidence: 99%
See 3 more Smart Citations